Upper Bound Collapse Load of Strip Footing that Rests on Unsaturated Sands - Prasad S.D.; Chakraborty M. (My University, 2025)
This paper attempts to investigate the bearing capacity of a strip footing that rested on unsaturated homogenous sands and used upper bound finite-element limit analysis in association with linear optimization. The analysis is based on suction stress-based (σs) effective stress (σ′) analysis. Unlike the saturated soil, the size of the yield surface varies with the vertical position, and therefore, proper modifications are carried out in the upper bound formulations to incorporate the unsaturated soil property functions. A detailed investigation is carried out to estimate the load-carrying capacity of a strip footing that vary the mechanical strength, unsaturated soil properties, water table depth (hw), and climatic conditions. The numerical solutions are presented in terms of bearing capacity factors [BCF (Nγs, Nqs)] for the unit weight (γw) and surcharge pressure (qs). The nodal velocity patterns are drawn for several cases, and the presented solutions are compared with the available results. The design charts provided in this paper might be useful to design engineers. © 2023 American Society of Civil Engineers.